1996
DOI: 10.1021/bi960038h
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of Anionic Porphyrins by DNA Aptamers

Abstract: DNA sequences were isolated by in vitro selection for binding to N-methylmesoporphyrin IX (NMM), a molecule that behaves as a stable transition-state analogue for porphyrin chelatases. Clones approximately 280 and approximately 120 nucleotides long were obtained, which bound to NMM with sub-micromolar affinity but bound mesoporphyrin IX (MPIX), as well as various metalloderivatives of MPIX, with lower affinity. Footprinting experiments with dimethyl sulfate, DNase I, and bound hemin molecules activated by supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
194
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(203 citation statements)
references
References 38 publications
6
194
0
3
Order By: Relevance
“…An aptamer for AMP has been coupled to fluorescent nanoparticles, thereby providing a highly selective sensor for that target 77. Besides this, aptamers have been reported for biologically relevant anionic porphyrins,78 again highlighting the possibilities for further exploitation in aqueous anion‐recognition chemistry. Very recently, DNA‐like oligomers with synthetic units replacing nucleobases were reported for pattern‐based detection of anion pollutants in water 79.…”
Section: Macromolecular Recognition Of Anions In Watermentioning
confidence: 96%
“…An aptamer for AMP has been coupled to fluorescent nanoparticles, thereby providing a highly selective sensor for that target 77. Besides this, aptamers have been reported for biologically relevant anionic porphyrins,78 again highlighting the possibilities for further exploitation in aqueous anion‐recognition chemistry. Very recently, DNA‐like oligomers with synthetic units replacing nucleobases were reported for pattern‐based detection of anion pollutants in water 79.…”
Section: Macromolecular Recognition Of Anions In Watermentioning
confidence: 96%
“…Therefore, the initial objective was to examine whether hemebinding aptamers could first, bind heme at this pH, and second, inhibit hemozoin formation. For this proof-of-concept study, we elected to use several previously reported heme-binding DNA aptamers (27,28) (Table 1), which were all discovered using SELEX carried out at pH 7-8.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, there is evidence that they can discriminate to some extent among different quadruplex folds [21,32,33]. Affinity chromatography using the selective quadruplex ligand N-methyl mesoporphyrin (NMM) coupled to acrylic beads has been used successfully to select quadruplexes from complex mixtures of nucleic acids [19,34], and so use of this ligand and probably others should be possible. Another approach would be to use well-defined quadruplex binding domains of proteins, but again, knowledge of the specificity of these domains is at an early stage.…”
Section: Affinity Purification and Tiling Array-based Analyses Of Genmentioning
confidence: 99%